Clarifying the scaling concept : A review, definition, and measure of scaling performance and an elaborate agenda for future research - Palmié, Maximilian; Parida, Vinit; Mader, Anna; Wincent, Joakim (Elsevier, 2023)
Scaling has recently found its way into the academic discourse. However, the term has been used inconsistently and mixed up with other terms such as growth. To overcome these impediments to knowledge accumulation, we review the literature, identifying four broad applications of the scaling concept: market scaling, volume scaling, financial scaling, and organizational scaling. Building on their commonalities and setting scaling apart from growth, we develop an inclusive definition of scaling: Scaling describes an increase in the size of a focal subject that is accompanied by a larger-than-proportional increase in the performance resulting from the said subject. We further propose a set of measures that makes it possible to compare the scaling performance of organizations and track their scaling performance over time. Based on our insights as well as a list of “hot topics” in the management literature, we conclude by identifying promising areas for further research.
Keywords: Hot topics in management research; Scaling; Scaling definition; Scaling measure; Scaling performance; Systematic literature review; fi=Strateginen johtaminen|en=Strategic Management|